Potential Role of Salivary and Urinary Amyloid-Β Biomarkers in Assessing Dementia Risk in Patients with Obstructive Sleep Apnea - Ece Defne Uzak; Tolga Yardımcı; Hatice Sabiha Türe; Aslı Subaşıoğlu (Izmir Katip Celebi University Faculty of Medicine, 2026)
Objective: Obstructive sleep apnea (OSA) is a prevalent sleep disorder characterized by repeated collapse of the upper airway during sleep, leading to intermittent episodes of apnea and hypopnea. This condition may negatively affect an individual's cognitive functions by causing fluctuations in oxygen saturation and sleep disruption throughout the night. Previous studies have revealed that OSA may be associated with the development of dementia. In the neurodegeneration process, which is one of the main causes of dementia, amyloid beta (Aβ) 1–40 and 1–42 proteins play an important role. In patients with OSA, it is thought that the removal of these proteins from the brain may be impaired, leading to toxic effects in nerve cells. Aβ1-40 and Aβ1-42 proteins are of great importance as biomarkers in the early diagnosis of dementia. Measurement of these biomarkers in patients with OSA may also contribute to new approaches for the early detection of dementia. To investigate salivary and urinary Aβ1–40 and Aβ1–42 levels, and evaluate the Aβ1–42/Aβ1–40 ratio as a potential non-invasive biomarker of dementia risk in patients with OSA. Materials and Methods: Twenty patients diagnosed with OSA and 15 age-matched healthy controls were included in this case-control study. Saliva and urine samples were collected from all participants. Aβ1–40 and Aβ1–42 concentrations were measured using commercially available enzyme-linked immunosorbent assay (ELISA) kits. The Aβ1–40 and Aβ1–42 levels were calculated for each sample and compared between groups. Results: Aβ1–40 levels were significantly higher in the OSA group compared with controls, whereas Aβ1–42 levels were higher in the control group. Consequently, the Aβ1–42/Aβ1–40 ratio was significantly lower in both saliva and urine samples in patients with OSA. These findings indicate a distinct alteration in peripheral amyloid profiles in OSA patients and suggest a potential shift toward a pro-amyloidogenic state. Conclusions: Salivary and urinary Aβ1-40 and Aβ1-42 profiles, particularly the Aβ1-42/Aβ1-40 ratio, may serve as promising non-invasive biomarkers for dementia risk stratification in patients with OSA. These results support the potential utility of peripheral amyloid measurements in early detection strategies prior to clinical dementia onset.